Razumevanje javnega potniškega prevozništva v turističnem gospodarstvu in potrebna ustrezna organiziranost - PAUKO, Franc (Promet - Traffic&Transportation, 2026)
CONCEPT OF PUBLIC PASSENGER SERVICES IN TOURIST INDUSTRY AND REQUIRED ORGANISATION This paper states the requirement for efficient transport services both in services provided for passengers – holiday-makers and transport of goods, particularly with the objective of adequate provision, i.e. supply of resort area/tourist destinations. The author illustrates the experiences of other countries in the world referring to high level of technical development of transportation means designed for passengers – tourists, requirements for the employment of polite and highly qualified personnel in this ‘sensitive’ industry segment, and discusses the problems experienced in rail, road, air and sea transport.